Inputdata for CESM2.3x compset F2000climo with spectral-element dynamical core.and refined grid over Greenland - Iaquinta, Jean (Zenodo, 2022)
Input data necessary to run a CESM2.3x case for the F2000 compset and a variable resolution mesh with a 1 degree global horizontal resolution grid and regional refinement of 1/4 degree resolution over the broader Arctic region plus an additionally 1/8 degree refinement over Greenland